Penerapan Data Mining Menggunakan Metode Cluster K-Means Untuk Pengelompokkan Fasilitas Sekolah - Faisal Muhammad; Suharmanto; Janu Ilham Saputo; Wiranti Sri Utami (Bulletin of Information Technology (BIT), 2025)
School Facilities are facilities provided by schools or universities to support activities and can be utilized by students, teachers, students and staff within the scope of a particular education. In order to create good teaching and learning activities (KBM) and support the development process and achievements, good schools or universities must have classroom facilities, laboratories, libraries, canteens, places of worship and fields. By applying data mining and utilizing the data sources obtained and the application of the K-Means cluster method, information related to school facilities can be drawn. The number of clusters obtained is 2 clusters with the number of squares according to the cluster of 76.0%.